Altered vegetation structure and composition linked to fire frequency and plant invasion in a biodiverse woodland - Fisher, J.; Loneragan, W.; Dixon, Kingsley; Delaney, J.; Veneklaas, E. (Elsevier, 2009)
Relationships between fire history, vegetation structure and composition, and invasion by introduced plant species have received limited attention in Australian woodlands. A study in a Mediterranean, fire adapted urban Banksia woodland remnant in the biodiversity hotspot of southwest Australia investigated: (1) Have significant changes occurred in the woodland tree canopy between 1963 and 2000? (2) Do correlations exist between fire frequency and canopy cover? (3) If there is a difference in the vegetation composition of Banksia woodland invaded by the South African Ehrharta calycina (PCe) and Pelargonium capitatum (PCp) compared to largely intact remnants (GC)? and (4) Do correlations exist between vegetation condition, composition, fire frequency and invasion? Aerial photography, processed in a Geographical Information System, was used to establish fire history and changes in canopy cover over time (1963-2000). PCe and PCp sites experienced the greatest number of fires, with a net reduction in canopy cover in all areas experiencing four or more fires (60% of all woodlands). Frequent fire corresponded with a decline in native cover, richness and diversity, a shift from native to introduced species, changes in the relative importance of fire response categories, and loss of native resprouting shrub cover. Life forms of introduced species, which included no trees, shrubs and perennial sedges, contrasted strongly with those of native species, which had poor representation of annual and perennial grasses. Clear ecological and conservation consequences due to the loss of species diversity, changes in fire ecology and invasion have occurred in the Banksia woodlands. This study provides an understanding of the invasion process, enhancing conservation knowledge to improve the adaptive management of the key threatening process of invasion in biodiverse communities. © 2009 Elsevier Ltd. All rights reserved.